Thermally assisted semiconductor-like to insulator transition in gold-poly(methyl methacrylate) nanocomposites - Abyaneh, Majid Kazemian; Pasricha, Renu; Gosavi, S. W.; Kulkarni, S. K. (Nanotechnology, 2006)
Gold-polymethylmethacrylate ( PMMA) nanocomposites were fabricated by mixing gold nanoparticles capped with oleylamine in polymethylmethacrylate. The samples were analysed using UV-vis absorption spectroscopy, transmission electron microscopy, small angle x-ray scattering, Fourier transform infrared spectrometry ( FTIR) and x-ray photoelectron spectroscopy ( XPS). Electrical resistivity of nanocomposite samples was measured by a four-probe technique in the 70-300 K range. The nanocomposites showed a transition with an onset at similar to 160-165 K. They exhibited a semiconductor-like conductivity at higher temperatures and nearly temperature independent conductivity at lower temperatures. The interfacial interaction of Au nanoparticles and PMMA polymer is investigated using FTIR and XPS. A ligand-exchange process occurs when capped gold nanoparticles are incorporated in PMMA polymer.

Titania nanoparticles synthesis in mesoporous molecular sieve MCM-41 - Lihitkar, N. B.; Abyaneh, Majid Kazemian; Samuel, V.; Pasricha, R.; Gosavi, S. W.; Kulkarni, S. K. (Journal of Colloid and Interface Science, 2007)
Nanocrystalline titanium oxide (TiO2) is one of the most useful oxide material, because of its widespread applications in photocatalysis, solar energy conversion, sensors and optoelectronics. The control of particle size and monodispersity of TiO2 nanoparticles is a challenging task. The use of MCM-41, an inorganic template of uniform pore size (2-10 nm), can overcome this difficulty and produce stable nanoparticles of uniform size and shape. Here, we demonstrate the synthesis of titania nanoparticles inside the pores of silica based MCM-41 forming a TiO2/Si-MCM composite. Composites are formed in the alcoholic medium by incipient wetness impregnation method. Titania particles of average 3 nm size are obtained. Effect of silica and titania precursors on the quality of nanoparticles has been investigated. The characterization of titania-MCM-41 composites has been carried out using a variety of techniques like UV-vis absorption spectroscopy, X-ray diffraction, FT-IR spectroscopy, X-ray photoelectron spectroscopy, transmission electron microscopy and photoluminescence spectroscopy. It has been found that the titania particles are co-ordinated with Si-MCM by Si-O-Ti covalent bond. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: incipient wetness impregnation; Mesoporous material; template; titania